THE DEVELOPMENT OF PASAR BARU AREA AS TOURIST DESTINATIONS IN CENTRAL JAKARTA - Dezury, Almadiva Esperanza; Auliya, Anisatul (Journal of Indonesian Tourism and Policy Studies, 2022)
The Purpose of this study to determine the efforts that can be made to increase the number of visitors to the Pasar Baru area, Central Jakarta because this area has a lot of tourist attractions that can be managed properly, that can become an attractive attraction in Pasar Baru area and also this area is full supported by the local government, which is always trying to develop tourism potential in Pasar Baru area. The research method used in this research is descriptive qualitative research method. Data collection was done by interview, observation, and literature study. This research activity was held from January -June 2021. Based on the results of research in the field that Pasar Baru area has various kinds of tourist activities that can be enjoyed by tourists such as: shopping, sight seeing, enjoying historical buildings, taking pictures and others. To make Pasar Baru as one of the tourist destinations of choice, the local government already has a planning for the development of the Pasar Baru tourist destination in the form of a revitalization plan for Pasar Baru area. Have to buils a good collaboration from all elements such as: business people, media partners, academics and the public who participate in the development of Pasar Baru Area as a one of favorite tourism destination in Central Jakarta.